Ask Question
15 July, 18:57

6 (2m-3) - 3m=2m-18+m what is m?

0
Answers (2)
  1. 15 July, 19:52
    0
    6 (2m-3) - 3m=2m-18+m

    distribute

    12m-18 - 3m = 2m-18 + m

    combine like terms

    9m-18 = 3m-18

    subtract 3m from each side

    6m - 18 = - 18

    add 18 to each side

    6m = 0

    divide by 6

    m=0
  2. 15 July, 20:36
    0
    6 (2m-3) - 3m=2m-18+m

    Step 1: Simplify both sides of the equation.

    6 (2m-3) - 3m=2m-18+m

    (6) (2m) + (6) (-3) + -3m=2m+-18+m (Distribute)

    12m+-18+-3m=2m+-18+m

    (12m+-3m) + (-18) = (2m+m) + (-18) (Combine Like Terms)

    9m+-18=3m+-18

    9m-18=3m-18

    Step 2: Subtract 3m from both sides.

    9m-18-3m=3m-18-3m

    6m-18=-18

    Step 3: Add 18 to both sides.

    6m-18+18=-18+18

    6m=0

    Step 4: Divide both sides by 6.

    6m

    6

    =

    0

    6

    m=0
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “6 (2m-3) - 3m=2m-18+m what is m? ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers